BUDGETING AND CATALOGING ENHANCEMENT FOR SMALL AND MEDIUM-SIZED ENTERPRISES TOWARDS SUSTAINABLE DEVELOPMENT GOALS - Halim, Velicia Faustine; Suhaimi, Hasnul (UI Scholars Hub, 2023)
This paper describes a business coaching activity for small and medium enterprises (SMEs) in chemical and waste management industries. Based on the analysis results, there was a lack of budgeting practice and suboptimal catalog marketing that comprised the majority of existing problems in SMEs. This research aims to assist the SME in improving its budgeting practice and product catalog. The method used is a qualitative method based on a business coaching approach. The research instruments adopted included in-depth individual interviews (IDI). The collected data was then processed and analyzed, starting with generating the SME's business process and service blueprint, followed by the business model canvas. Next, the paper also covers external and internal analyses, followed by the Gap and Pareto analyses to identify the priority issues. The owners of the SME have set a target to expand their business. However, various shortcomings can hinder the business. Most research finds that SMEs usually tend to be characterized by less financial planning, including the SME in this research. Many kinds of literature debate how to develop a budgeting process for SMEs as the vast majority of literature on management accounting for SMEs is still under-researched. Formulating a meaningful operating budget can give the business clear goals. The second issue is related to the catalog, which is one of its critical marketing channels. However, the catalog has not yet been enriched with better-quality content compared to the competitors. The research results have the potential to deliver positive improvements for SMEs across similar cases. Further, the contribution of this study may guide owners of businesses and policy-makers on how to develop guidance for SMEs to solve their issues with practical assistance in the future.